ENDOGENOUS RECOMBINANT GROWTH AND INTELLECTUAL PROPERTY RIGHTS. (4th September 2017) - Marchese, Carla; Marsiglio, Simone; Privileggi, Fabio; Ramello, Giovanni B.
Abstract : We show that, even in a framework in which monopolistic exploitation of patents does not occur, patents still give rise to serious drawbacks. We rely on a recombinant growth framework that provides a stylized but clear description of the formation of knowledge externalities. In our setting a benevolent government buys immediately new patents in a competitive market and releases their contents for free. We show that inefficiencies nevertheless arise and welfare can be improved by correcting the market price through a tax–subsidy scheme. We characterize the (asymptotic) steady-state equilibrium, and some properties of the transitional path. We show that if certain conditions are met, then the economy will converge to its (asymptotic) balanced growth path, and along such a pathgrowth will be independent of the policy parameter; conversely, transition dynamics are affected by the choice of the policy parameter. We then quantitatively analyze the effect of different policy interventions on welfare, and show that stricter tax (weaker appropriability) regimes lead to higher social welfare.